Intuitions and Experiments: A Defense of the Case Method in Epistemology. - Nagel, Jennifer (Philosophy & Phenomenological Research, 2012)
The article offers the author's insights concerning the intuitions and experiments to defend a case method in epistemology. The author agrees with the experimentalists who consider the question of epistemic intuition's epistemic status as an excellent question. She adds that intuitive judgment mechanics reveal some of the deep similarities between perception and epistemic intuition.